Alih Kode Dan Campur Kode Dalam Interaksi Masyarakat Terminal Motabuik Kota Atambua - Anggelina Theresia Pires; Liliana Ximenes; Maria Elisabeth Bria; Oktaviana Orleans; Raimires Mario Lordes Bria; Adrianus Berek (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research aims to describe the use of language in community interactions at the Motabuik terminal, Atambua City. The use of language in question is the form and function of code switching and code mixing in the interaction of the Motabuik Terminal Community, Atambua City. The data referred to in this research is code switching and code mixing in the interactions of the Atambua City Terminal Community, in the form of speech between the Motabuik Terminal Community. The speech in question is in the form of a conversation containing words, phrases, clauses and sentences that have elements of code switching and code mixing. Data collection was carried out using listening, note-taking and introspection techniques. Data analysis techniques were carried out with all utterances that showed the occurrence of code switching and code mixing in interactions at the Motabuik Terminal, Atambua City which contained elements of code switching and code mixing. Data collection was carried out by listening, taking notes and introspection. Data analysis techniques were carried out with all utterances that showed the occurrence of code switching and code mixing in the interaction of the Motabuik Terminal community, Atambua City, identified and carded complete with their construction. Next, classification and categories of the overall data are carried out. The data was analyzed by selecting and sorting out the forms and functions of code switching and code mixing in the interactions of the Motabuik Terminal Community, Atambua City. After being analyzed and classified, the data is described and explained to find out the form and function of code switching and code mixing in the interaction of the Motabuik Terminal Community, Atambua City. The results of the research show that there are two types of code switching in the interaction discourse at the Motabuik Terminal, namely in the form of language transfer, includes code switching from Atambua language to Indonesian and code switching from Indonesian to Atambua language at the Motabuik terminal, namely internal code mixing in the form of Atambua language words and phrases and connecting Indonesian as a unifying language communication tool at the terminal, the code mixing function has aspects speech, to explain, provide information and respect passengers.